Caffeine Induces Autophagy and Apoptosis in Auditory Hair Cells via the SGK1/HIF-1α Pathway - Tang, Xiaomin; Sun, Yuxuan; Xu, Chenyu; Guo, Xiaotao; Sun, Jiaqiang; Pan, Chunchen; Sun, Jingwu (Frontiers in Cell and Developmental Biology, 2021)
Caffeine is being increasingly used in daily life, such as in drinks, cosmetics, and medicine. Caffeine is known as a mild stimulant of the central nervous system, which is also closely related to neurologic disease. However, it is unknown whether caffeine cause hearing loss. and there is great interest in determining the effect of caffeine in cochlear hair cells. First, we explored the difference in Auditory Brainstem Response (ABR), organ of Corti, stria vascularis, and spiral ganglion neurons between the control and caffeine-treated groups of C57BL/6 mice. RNA sequencing was conducted to profile mRNA expression differences in the cochlea of control and caffeine-treated mice. A CCK-8 assay was used to evaluate the approximate concentration of caffeine. Flow cytometry, TUNEL assay, immunocytochemistry, qRT-PCR, and western blotting were performed to detect the effects of SGK1 in HEI-OC1 cells and basilar membranes. In vivo research showed that 120mg/kg caffeine injection caused hearing loss by damaging the organ of Corti, stria vascularis, and spiral ganglion neurons. RNA-seq results suggested that SGK1 might play a vital role in ototoxicity. To confirm our observations in vitro, we used the HEI-OC1 cell line, a cochlear hair cell-like cell line, to investigate the role of caffeine in hearing loss. The results of flow cytometry, TUNEL assay, immunocytochemistry, qRT-PCR and western blotting showed that caffeine caused autophagy and apoptosis via SGK1 pathway. We verified the interaction between SGK1 and HIF-1α by co-IP. To confirm the role of SGK1 and HIF-1α, GSK650394 was used as an inhibitor of SGK1 and CoCl2 was used as an inducer of HIF-1α. Western blot analysis suggested that GSK650394 and CoCl2 relieved the caffeine-induced apoptosis and autophagy. Together, these results indicated that caffeine induces autophagy and apoptosis in auditory hair cells via the SGK1/HIF-1α pathway, suggesting that caffeine may cause hearing loss. Additionally, our findings provided new insights into ototoxic drugs, demonstrating that SGK1 and its downstream pathways may be potential therapeutic targets for hearing research at the molecular level.